(untitled) (CIPEEX, 2025)
Introduction: The stress experienced by sexual and gender minorities, including internalized prejudice and anticipated discrimination, significantly impacts the mental health of this population. Objective: To review the literature on risk factors associated with mental disorders in sexual and gender minorities in Brazil. Methods: This is an integrative review using the PICO strategy. Studies published in the last five years, with a cross-sectional design, in English or Portuguese were included. Searches were conducted in August 2025 in the PubMed and SciELO databases, using the descriptors: Risk factors AND mental disorders AND sexual minorities OR gender AND Brazil. Of the 35 studies identified, four met the inclusion criteria. Results: Internalized prejudice and anticipated discrimination were strongly associated with depression, anxiety, and suicide risk. Conversely, social support and identity affirmation were shown to be important protective factors. Conclusion: Sexual and gender minorities are more vulnerable to mental disorders due to internalized prejudice and anticipated discrimination, while social support and identity affirmation act as protective factors, highlighting the need for inclusive mental health promotion strategies.